Composição e distribuição espacial da meiofauna, com ênfase na nematofauna, em praias arenosas da ilha de Trindade (Brasil) - NASCIMENTO, Wanessa Coimbra (2019)
The aim of this work was to characterize horizontally and vertically the structure of meiobenthos community in two beaches of Trindade Island, with emphasis in Nematoda. The samplings were made during summer (December) of 2014, in two beaches, Portugueses and Príncipe, in three zones of intertidal region, upper intertidal (MLS), medium (MLM) and lower (MLI) and in two sediment layers, Superior (0-10 cm) and Inferior (10-20 cm). The samples were collected with a corer of 3cm inner diameter and 10 cm of length and fixed in formol 4%. Additional sediment samples were collected for granulometric analysis and temperature and salinity were measured in the local. In laboratory, the organisms were isolated from sediment with manual elutriation, counted and identified in major zoological groups. The animals of Nematoda group were isolated, diafanized, mounted on permanent slides and identified up to species level. For the different groups of organisms, density, richness, diversity and equitativity were calculated. The descriptors were compared between beaches, zones and layers using univariate (ANOVA’s) and multivariate (PERMANOVA, MDS, SIMPER, PCA and BIOENV) analyses. The meiobenthic community was composed of 7 groups, with Oligochaeta and Nematoda as the most abundant groups. The highest meiofauna and nematofauna densities on Trindade Island were found on the Portugueses Beach in the upper intertidal region. Meiofauna varied between beaches, zones and sediment layers, however nematofauna varied only between the beaches and zones. The BIOENV analysis showed that mean grain size is the main variable that defines meiofauna distribution and degree of sediment selection is considered as the variable that best explains the distribution of nematofauna. Nematofauna was composed of 26 species, mainly selective detritivores, with Theristus sp.1. as the most abundant.